Contemporary photography practice: From landscape to expanded modes of place representation - Hill, Rodrigo (2021)
Contemporary photographic practice has evolved into a broad field of possibilities, a flux of representational modes that represent emotions, experiences and feelings. In parallel the depth and layering of places offers a stimulating challenge to researchers and artists whom are willing to creatively explore nuances of land and nature as well as the multi-sensorial and spatial “reality” of places. The Waikato River is my research locale, located in the central North Island of Aotearoa New Zealand. I draw on contemporary photography practice and theory to develop multimodal approaches to my research place, expanding objective modes of landscape and place representation. I trace a timeline from early landscape photography practice particularly during the British colonisation in New Zealand juxtaposing my photography practice as a counter approach to Eurocentric modes of place representation. This is informed by local Waikato Māori cosmologies and more contemporary readings on place. As a result  I conceptualised a theoretical framework around the notion of place imaginaries as a creative platform for the development of expanded photographic modalities.